THE IMPACT OF E-MONEY ON INFLATION IN INDONESIA - IWAN HARSONO (GANEC SWARA, 2023)
The purpose of this study was to estimate the influence of using e-money on the inflation rate in Indonesia, using research data in the form of monthly time series data for e-money payments and inflation for 2016-2021 collected from www.bi.go.id, www.bps.go.id/, and www.kemendag.go.id/. This research is quantitative in nature. Regression analysis is a data analysis technique. H0 = Using e-money has no significant influence on the inflation rate; H1 = Using e-money has a substantial effect on the inflation rate. As a result, e-money affects inflation by 0.298 (29.8%). Because t counts t table, H0 is accepted, implying that utilizing e-money has no major effect on the inflation rate. The result is that e-money affects 0.298 (29.8%) inflation. Because t count <t table, H0 is accepted, which means that there is no significant effect of using e-money on the inflation rate. The regression model is Y = 25.237 + 0.583X. With β = 0.435, assuming the use of e-money has a fixed (unchanging) value, then every increase in e-money by 1 unit will increase the inflation rate by 0.583. The conclusion is that using e-money does not significantly affect the inflation rate.